SENGKARUT REGULASI: URGENSI PEMBENTUKAN LEMBAGA KHUSUS LEGISLASI DI INDONESIA - Dewi, Ni Luh Putu Geney Sri Kusuma; Sari, Ni Putu Riyani Kartika (Jurnal Hukum Saraswati (JHS), 2019)
Regulation is an instrument for realizing state policies in order to achieve the objectives of the state. As an instrument to realize every state policy, regulations must be formed in the right way so that they are able to produce good regulations and be able to encourage the implementation of orderly social dynamics and be able to encourage the performance of state administration. Indonesia is currently experiencing problems in regulation such as over regulation, overlapping and low quality of legislation. Regulatory disputes that occur become a very urgent problem to be addressed immediately. One way to overcome this is to improve the quality of product legislation and establish a single institution that manages regulation. The institution will later be responsible for establishing legislation at the Government level and also efforts to establish a system of regulation that is integrated in one door and systematic.